2021
DOI: 10.13170/ajas.6.2.20374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coccidia in domestic pigeons (Columba livia domestica Gmelin, 1789) in Benghazi city, Libya

Abstract: Pigeon coccidiosis is caused by Eimeria spp; a protozoan parasite which limits birds’ productivity by causing severe illness. The current study was carried out to investigate the prevalence of coccidiosis on domestic pigeon in Libya. Intestinal contents of 100 pigeons (Columba livia domestica Gmelin, 1789) were collected within a period of five months; January to May 2020. The intestinal content was examined to detect of coccidian oocysts infection on the randomly selected birds. A total of 100 faecal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
1
1
Order By: Relevance
“…Previous studies have shown that the incidence of coccidia infection in birds varies. Incidence of coccidia in birds in Libya was found at 72% [18], whereas the lower incidence of coccidia infection (16%) was reported in Surabaya, Indonesia [19]. In this study, 28 out of 94 (30%) were positive for coccidial oocysts.…”
Section: Resultscontrasting
confidence: 59%
“…Previous studies have shown that the incidence of coccidia infection in birds varies. Incidence of coccidia in birds in Libya was found at 72% [18], whereas the lower incidence of coccidia infection (16%) was reported in Surabaya, Indonesia [19]. In this study, 28 out of 94 (30%) were positive for coccidial oocysts.…”
Section: Resultscontrasting
confidence: 59%
“…When comparing the oocysts detected in the present study with the group of E. labbeana species previously described from the Columbidae, the following findings can be made: (i) The oocyst studied in this study, or those from Australia, was far from the type locality of E. labbeana . (ii) The morphometric data of the oocysts showed variation in the size of the oocysts which were larger than that described by Nieschulz ( 12 ), Joseph et al ( 46 ), Aboelhadid et al ( 52 ), Al-Agouri et al ( 53 ), and Oliveira et al ( 30 ). (iii) The oocyst shape of E. labbeana was spherical to subspherical except for those described by Pinto ( 18 ), Nieschulz ( 12 ), Aboelhadid et al ( 52 ), and Oliveira et al ( 30 ) who highlighted the polymorphic nature of the oocysts, which could be sub-spherical and/or ellipsoidal.…”
Section: Discussionmentioning
confidence: 67%
“…(iv) There was no micropyle except for those identified by Pinto ( 18 ) and Oliveira et al ( 30 ). (v) There was no oocyst residuum except for those described by Al-Agouri et al ( 53 ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations